Determining salivary and serum levels of iron, zinc and vitamin B12 in patients with geographic tongue - Mina Khayamzadeh; Shamsoulmolouk Najafi; Parastoo Sadrolodabaei; Faranak Vakili; Mohammad Javad Kharrazi Fard (Tabriz University of Medical Sciences, 2019)
Background. Benign migratory glossitis or geographic tongue, whose cause still remains a mystery, emerges as annular lesions on the dorsal surface of the tongue. Several reasons have been reported for this condition, including vitamin deficiencies, digestive disorders, emotional stress and nutritional deficiencies. In order to introduce an efficient treatment for the geographic tongue, the present study investigated the levels of iron, zinc and vitamin B12 in the blood and saliva. Methods. The present study evaluated 40 subjects. The oral disease specialists examined the patients in the Dental School, Tehran University International Campus and Mashhad Dental School. Accordingly, inclusion and exclusion criteria were used to enroll the patients. The blood and salivary samples were collected from the case and control groups. Finally, independent t-test was used to analyze the data. Results. Overall, 20 subjects suffered from geographic tongue. They consisted of 8 females and 12 males, with a mean age of 33.5±4.8 and age range of 19‒49 years. Moreover, the mean age and age range of the healthy subjects were 29.40±7.5 and 24‒25 years, respectively. It should be pointed out that the subjects were equally divided into 10 males and 10 females. There was no difference between other variables in the blood and saliva. Conclusion. The results showed that patients with geographic tongue had lower levels of salivary zinc, compared to the control group. Although iron and vitamin B12 affect the lingual papillae, their serum and salivary levels did not change.